1997
DOI: 10.1139/e17-030
|View full text |Cite
|
Sign up to set email alerts
|

Ni, Cu, Au, and platinum-group element contents of sulphides associated with intraplate magmatism: a synthesis

Abstract: The tectonic setting of intraplate magmas, typically a plume intersecting a rift, is ideal for the development of Ni -Cuplatinum-group element-bearing sulphides. The plume transports metal-rich magmas close to the mantle-crust boundary. The interaction of the rift and plume permits rapid transport of the magma into the crust, thus ensuring that no sulphides are lost from the magma en route to the crust. The rift may contain sediments which could provide the sulphur necessary to bring about sulphide saturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 29 publications
1
15
0
3
Order By: Relevance
“…Their Pt/Pd is 0.7, in sharp contrast to the internal Bushveld PGE reefs (Merensky Reef, UG2 chromitite) which have Pt/Pd significantly above unity (Maier et al 2013), but resembling the lower portions of the Platreef that have Pt/Pd <1 (Kinnaird 2005). Barnes et al (1997) have shown that certain sulphide deposits have lower Pt/Pd than their parent magmas and suggested that this is due to higher D Pd than D Pt into sulphide liquid. Based on this argument, one could propose that the relatively low Pt/Pd at Uitkomst is a result of the relative sulphide enrichment of the intrusion.…”
Section: Interpretation Of Chalcophile Metal Datamentioning
confidence: 95%
“…Their Pt/Pd is 0.7, in sharp contrast to the internal Bushveld PGE reefs (Merensky Reef, UG2 chromitite) which have Pt/Pd significantly above unity (Maier et al 2013), but resembling the lower portions of the Platreef that have Pt/Pd <1 (Kinnaird 2005). Barnes et al (1997) have shown that certain sulphide deposits have lower Pt/Pd than their parent magmas and suggested that this is due to higher D Pd than D Pt into sulphide liquid. Based on this argument, one could propose that the relatively low Pt/Pd at Uitkomst is a result of the relative sulphide enrichment of the intrusion.…”
Section: Interpretation Of Chalcophile Metal Datamentioning
confidence: 95%
“…Des chercheurs (Lesher 1993;Ripley, 1981;Thériault et al, 1997;Barnes et al, 1997) ont mis en évidence la contamination comme étant le principal processus provoquant la saturation du magma en soufre et par conséquent, la formation de gisements de sulfures magmatiques. Les magmas qui proviennent du manteau sont, de L'assimilation du matériel crustal peut se faire : 1) Par la fusion du matériel solide (Watson 1982;Thériault et al, 1997), 2) Par dégazage lié à la mise en place du magma dans l'encaissant et les xénolithes lors du métamorphisme de contact, (Ripley, 1981), 3) La contamination peut se faire aussi par mélange de magmas (Emslie, 1978).…”
Section: Contaminationunclassified
“…La teneur en forstérite des olivines des roches riches en oxydes de fer de Boulder Lesher (1993), Ripley, (1981), Thériault et al, (1997 et Barnes et al, (1997) …”
Section: éVolution Du Magmaunclassified
See 1 more Smart Citation
“…1. Conceptual model for fluid transport of sulfur from country rocks into magma, after Barnes et al (1997). The hypothesis is that the intrusion of magma raises country-rock temperatures above the stability of pyrite (white squares), which breaks down to pyrrhotite + S 2 .…”
Section: (Traduit Par La Rédaction)mentioning
confidence: 99%